ANALISIS YURIDIS PENDAFTARAN PERALIHAN HAK GUNA BANGUNAN AKIBAT PEWARISAN SECARA AB INTESTATO DI KOTA MEDAN - BERLIANA YUNITA HUTAGALUNG (PREMISE LAW JURNAL, 2014)
ABSTRACT According to law of inheritance (ab intestate), inheritance constitutes a determining factor in which there is the relationship between a testator and an heir. In the registration of the transfer of building rights because of inheritance, the heir becomes entitled to the building rights when the person entitled to it or the testator dies. Who will be the heirs is regulated by the applicable law for heirs. The transfer of rights because inheritance should be registered in the Land Office, according to the stipulation in the Government Regulation No. 24/1997 on Land Registration in order to give legal certainty, provide information, and establish land administrative regulation. The result of the research showed that Registering the transfer of building rights as the result of inheritance as ab intestate in the Land Office, Medan, as the transfer based of building rights, was by presenting certificate of inheritance based on the classification of population. Keywords: Transfer of Land Rights, Ab intestate, Building Rights